2021
DOI: 10.3390/ani11020445
|View full text |Cite
|
Sign up to set email alerts
|

Chronological Expression of PITX2 and SIX1 Genes and the Association between Their Polymorphisms and Chicken Meat Quality Traits

Abstract: Meat quality is closely related to the development of skeletal muscle, in which PITX2 and SIX1 genes play important regulatory roles. The present study firstly provided the data of chronological expression files of PITX2 and SIX1 genes in the post-hatching pectoral muscle and analyzed the association of their polymorphisms with the meat quality traits of Wuliang Mountain Black-bone (WLMB) chickens. The results showed that both PITX2 and SIX1 genes were weakly expressed in the second and third weeks, and then i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 34 publications
(22 reference statements)
0
7
0
1
Order By: Relevance
“… 20 Recently, 4 SNPs (g.9830C > T, g.13335G > A, g.10073 C > T, g.13726A > G) of the PITX2 gene showed significant association with chicken meat quality. 13 However, the literature about PITX2 variation in Awassi sheep is rare.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 20 Recently, 4 SNPs (g.9830C > T, g.13335G > A, g.10073 C > T, g.13726A > G) of the PITX2 gene showed significant association with chicken meat quality. 13 However, the literature about PITX2 variation in Awassi sheep is rare.…”
Section: Discussionmentioning
confidence: 99%
“… 11 PITX2 , also known as RIEG , influences hematopoiesis, differentiation, and organogenesis. 12 , 13 PITX2 expression results in the expression of all genes in our asymmetry marker panel, including ERα , which may contribute to sexual differentiation. Paired-like homeodomain transcription factor 2 also controls the bone morphogenetic protein 7 (BMP7) gene, which is present in the left gonad at the beginning of its development.…”
Section: Introductionmentioning
confidence: 99%
“…g.102G > A was significantly associated with shank diameter at 63 days. g.197G > A was significantly associated with shank diameter at 49 days, the crude protein content of leg muscle, and other traits [ 23 ]. The two sites, g.102G > A and g.255G > A, are the same as the coding region in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Paired-like homeodomain transcription factor 2 (PITX2) and paired-like homeodomain transcription factor 1 (PITX1) are important transcription factors, which were highly expressed in skeletal muscle and modulate skeletal muscle development and organ morphogenesis [42][43][44]. Multiple studies have shown that PITX2 was correlated signi cantly with the growth traits and meat quality of chickens, pigs, cattle, sheep, and other animals [44][45][46][47][48][49][50]. Mice with overexpressed PITX1 exhibited decreased body weight, muscle mass, muscle strength, and atrophic muscle bers [51].…”
Section: Skeletal Musclementioning
confidence: 99%